EKSISTENSI POS BANTUAN HUKUM DALAM MEMBERIKAN BANTUAN HUKUM DI PENGADILAN AGAMA KELAS I B WATAMPONE - Rosita, Rosita (Institut Agama Islam Negeri (IAIN) Bone, 2017)
One of the provision of legal service for the community in court is the establishment of legal aid post. A court legal aid post is a service established by and in any first instance court to provide legal service in the form of legal information, consultation and advice and the creation of required legal documents. The existence of a law courthouse aid post of class IB Watampone is very helpful to the duties of clerks and judges. So that legal service becomes more effective and efficient. But some obstacles faced by legal aid post in legal services that not cooperative plaintiffs, facilities and minimal infrastructure, and knowledge of legal officers are still lacking.